The legume-rhizobia relationship in the Mediterranean basin - Howieson J.G.; O'Hara G.W.; Loi A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
To effectively harness the value of symbiotic N-fixation we need to understand G2 x E, where G refers to the genotypes of both legume and microsymbiont, and E the edaphic environment in which the symbiosis is to function. In the Mediterranean basin there is strong evidence that despite co-evolution of legumes and rhizobia, the relationship is not always optimal. Several research options are presented to improve N-fixation depending on the nature of the limitation to legume or rhizobial performance.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)